2020
DOI: 10.3389/fpls.2020.00527
|View full text |Cite
|
Sign up to set email alerts
|

R2R3-MYB Transcription Factors Regulate Anthocyanin Biosynthesis in Grapevine Vegetative Tissues

Abstract: Anthocyanins with important physiological functions mainly accumulate in grape berry, but teinturier grape cultivars can accumulate anthocyanins in both reproductive and vegetative tissues. The molecular regulatory mechanisms of anthocyanin biosynthesis in grapevine reproductive and vegetative tissues are different. Therefore, teinturier grapevine cultivar provides opportunities to investigate transcriptional regulation of vegetative anthocyanins, and to compare with mechanisms that regulate grape berry anthoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 41 publications
(90 reference statements)
4
26
0
Order By: Relevance
“…MYBA1 and MYBA2 at the color locus are the major genetic determinants of grape skin color, and the mutation of two functional genes (VvMYBA1, VvMYBA2) from these loci lead to white skin color ( Jiu et al, 2021 ), while VvMYB86 can inhibit anthocyanin biosynthesis primarily in grape berry by downregulating the expression of two structural genes including VvANS and VvUFGT ( Cheng et al, 2021 ). Transcriptome and metabolic data revealed that up-regulated expression of VvMYBA1, VvMYBA5, VvMYBA6 and VvMYBA7 are responsible for the specific anthocyanin patterns of Yan73 vegetative tissues, with VvMYB5A and VvMYB6A likely encoding the major regulators of anthocyanin biosynthesis in Yan73 vegetative tissues, simultaneously, VvMYBC2-L1 and VvMYBC2-L3, as repressor genes, are activated and may negatively regulated anthocyanin biosynthesis in vegetative tissues, therefore maintaining the balance of anthocyanin level ( Xie et al, 2020 ). VvMYBPA1 did not activate the promoter of VvUFGT , which encodes the anthocyanin specific flavonoid-3- O -glucosyltransferase, while activated the expression of VvLAR and VvANR and further regulate the proanthocyanidin synthesis, indicating that tissue and temporal-specific expression of VvANR and VvLAR correlates with proanthocyanidins (PAs) accumulation prior to veraison in grapes ( Bogs et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…MYBA1 and MYBA2 at the color locus are the major genetic determinants of grape skin color, and the mutation of two functional genes (VvMYBA1, VvMYBA2) from these loci lead to white skin color ( Jiu et al, 2021 ), while VvMYB86 can inhibit anthocyanin biosynthesis primarily in grape berry by downregulating the expression of two structural genes including VvANS and VvUFGT ( Cheng et al, 2021 ). Transcriptome and metabolic data revealed that up-regulated expression of VvMYBA1, VvMYBA5, VvMYBA6 and VvMYBA7 are responsible for the specific anthocyanin patterns of Yan73 vegetative tissues, with VvMYB5A and VvMYB6A likely encoding the major regulators of anthocyanin biosynthesis in Yan73 vegetative tissues, simultaneously, VvMYBC2-L1 and VvMYBC2-L3, as repressor genes, are activated and may negatively regulated anthocyanin biosynthesis in vegetative tissues, therefore maintaining the balance of anthocyanin level ( Xie et al, 2020 ). VvMYBPA1 did not activate the promoter of VvUFGT , which encodes the anthocyanin specific flavonoid-3- O -glucosyltransferase, while activated the expression of VvLAR and VvANR and further regulate the proanthocyanidin synthesis, indicating that tissue and temporal-specific expression of VvANR and VvLAR correlates with proanthocyanidins (PAs) accumulation prior to veraison in grapes ( Bogs et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, all of 15 transcripts associated with JA biosynthesis identified by MapMan analysis were found to respond to HL stress and were up-regulated by HL ( Figure 8 A). Several studies have reported that JA mediates the biosynthesis and accumulation of anthocyanins in plants when they are exposed to adverse environmental conditions [ 40 , 42 , 44 , 45 ]. In our study, RT-qPCR analysis of five JA biosynthesis-associated genes also indicated that the expression of all of them was induced in rapeseed leaves by HL stress, supporting the results of the transcriptome analysis ( Figure 8 B).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous previous studies have reported on anthocyanin biosynthesis-associated genes and their role in the regulation of color phenotypes and tolerance to HL stress [ 79 , 80 , 81 ]. The functions of these genes have also been studied in detail using overexpression and/or silencing strategies in Arabidopsis or other plant species, such as apple [ 82 ], grape [ 42 ] and wheat [ 50 ]. Documenting the transcriptional expression of key anthocyanin biosynthesis-related genes may provide further insight into plant response to HL stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these transcription factors, MYB transcription factors play a significant role in regulating anthocyanin biosynthesis. Many anthocyanin-related R2R3-MYB factors have been identified from many plants such as Arabidopsis [39], grape [53], Gerbera [54], eggplant [55], tomato [55], populous [56], apple [57,58], etc. Most of these are R2R3-MYB proteins with the motif [D/E]LX2[R/K]X3LX6LX3R in the R3 domain, which is necessary to interact with bHLH acting as activators to increase anthocyanin accumulation [59].…”
Section: The Activation Of Positive R2r3-myb Factors Is Sufficient For Promoting Anthocyanin Biosynthesismentioning
confidence: 99%